Electrical and optical properties of diffuse coplanar surface barrier discharge - Akildinova, A.K.; Ussenov, Y.A.; Pazyl, A.S.; Gabdullin, M.T.; Dosbolayev, M.K.; Ramazanov, T.S.; Daniyarov, T.T. (Recent Contributions to Physics, 2018)
In this paper, the electrical and optical properties of a dielectric coplanar surface barrier discharge (DCSBD) were studied. The current-voltage characteristic and the emission spectrum of a dielectric coplanar surface barrier discharge were obtained. A dynamic current-voltage characteristic was obtained with using the Rogowski Belt, a high-voltage probe, and an oscilloscope with high resolution. In order to further study the processing of various materials, the surface temperature of the RPS400, on which the plasma was ignited, was measured. The surface temperature was measured with a pyrometer. The results of investigations of the electrical properties of DCSBD showed that the discharge character is capacitive with the observed conduction current peaks above the bias current that arise from the presence of single micro-discharge channels. The results of optical emission spectroscopy showed the presence of molecular bands of nitrogen in the emission spectrum of DCSBD, namely, the second positive (N2 (C-B)) and the first negative (N2+ (B-X)) systems, as well as low-intensity OH and NO lines.